Clinical experience with microdialysis catheters in pediatric liver transplants. Issue 3 (11th March 2013) - Haugaa, Håkon; Almaas, Runar; Thorgersen, Ebbe Billmann; Foss, Aksel; Line, Pål Dag; Sanengen, Truls; Bergmann, Gísli Björn; Ohlin, Per; Wælgaard, Lars; Grindheim, Guro; Pischke, Soeren Erik; Mollnes, Tom Eirik; et al.
<x xml:space="preserve">Abstract</x> Ischemic vascular complications and rejection occur more frequently with pediatric liver transplants versus adult liver transplants. Using intrahepatic microdialysis catheters, we measured lactate, pyruvate, glucose, and glycerol values at the bedside for a median of 10 days in 20 pediatric liver grafts. Ischemia (n = 6), which was defined as a lactate level > 3.0 mM and a lactate/pyruvate ratio > 20, was detected without a measurable time delay with 100% sensitivity and 86% specificity. Rejection (n = 8), which was defined as a lactate level > 2.0 mM and a lactate/pyruvate ratio < 20 lasting for 6 or more hours, was detected with 88% sensitivity and 45% specificity. With additional clinical criteria, the specificity was 83% without a decrease in the sensitivity. Rejection was detected at a median of 4 days (range = 1‐7 days) before alanine aminotransferase increased (n = 5, P = 0.11), at a median of 4 days (range = 2‐9 days) before total bilirubin increased 25% or more (n = 7, P = 0.04), and at a median of 6 days (range = 4‐11 days) before biopsy was performed (n = 8, P = 0.05). In conclusion, microdialysis catheters can be used to detect episodes of ischemia and rejection before current standard methods in pediatric liver transplants with clinically acceptable levels of sensitivity and specificity. The catheters were well tolerated by the children, and no major complications related to the catheters were observed. Liver Transpl 19:305–314, 2013. © 2013 AASLD.